PRACTICAL ASPECTS OF REALIZATION OF THE DEVELOPMENT STRATEGY IN THE TOURISM REGION - Rukomoinikova, Vera; Zykova, Nadezhda; Tumbaeva, Iraida (Journal of Applied Engineering Science, 2016)
Many authors have turned their research interests to the problem of efficiency of the tourism development strategy realization. It was the result of the fact that growth and implementation of the tourism development strategies appears to be the common world trend of the last decade. This research focuses on the territorial level. The paper concentrates on the small region of the central part of Russia through the example of which the authors want to retrace the realization of the tourism development strategy adopted by the municipal authorities. The major aim of the study has several objectives associated with the theoretical analysis of practical aspects of the tourism development problem in the region. First of all, there is a need to provide a review of the literature devoted to the regional tourism efficiency evaluation. Secondly, it is necessary to measure the tourism efficiency in the region on the quantitative and qualitative level. The quantitative level refers to statistic data about the regional tourism. The qualitative level includes case study with self-employed individuals who set up their business in the field of rural tourism. Finally, this study has an overarching objective to identify the opportunities for the touristic potential of the small agricultural region of Mari El. It is quite currently important for the region to reveal the patterns according to which an insertion of private sector in the rural tourism development takes place. The research is based on international academic literature and the analysis of Russian experience.